Evaluating Knowledge-Oriented Management: An Iranian University Case Study - Anvari, Alireza; Mohd. Yusuff, Rosnah; Zulkifli, Norzima; Hojjati, Mohammad Hossein; Ismail, Yusof (Journal of Knowledge Management Practice, 2010)
The rapid change in science and technology bring in widespread changes in many different areas has challenged organizations managers. Hence to survive and compete in dynamic and unpredictable situations, they have to revise their policies directed and their leadership styles in the proper directions. One of these innovative instruments is knowledge management which can play an effective role in Iranian organizations specifically in universities. The major objective of the present study is to identify and measure the promotion of knowledge - oriented management in universities.The research methodology comprised of both; qualitative and quantitative method. A literature review of knowledge management in the university was collected. Data obtained from 124 participants (more than 40% of the population) has been analyzed. The instrument used was a standardized questionnaire on knowledge management of which the internal correlation was calculated through Cronbach’s alpha of 92%, and then analyzed using SPSS, and was measured through t test and Pearson correlation. In this study, besides descriptive statistics methods, depending on the type of variable, t test and correlation coefficient were applied for investigating the correlation.In general, the findings indicated that: There are some tokens of knowledge- oriented management which were above the medium level (strategic vision and leadership), the indexes for human resources and general management were average, but especially internal process was lower than average. The embracement of knowledge management was following an increasing pace. Also the result showed, there was a significant difference between two groups (lecturer and staff) perception and experience of Knowledge – oriented management in the university. Furthermore, there are some evidences such as software and hardware networks, resources, conducting training, creating cultural basis, budgeting on research etc, imply the trend of Knowledge- oriented management development.
Keywords: Knowledge management; Knowledge-oriented; Measurement; Indicator; University